Saliva inhibits the chemiluminescence response, phagocytosis, and killing of Staphylococcus epidermidis by polymorphonuclear leukocytes. - Saito, K (1988)
Saliva inhibited several functional properties of polymorphonuclear leukocytes (PMNs) from murine peritoneal exudate, namely, luminol-mediated chemiluminescence (CL) induced by either Staphylococcus epidermidis or formylmethionyl-leucyl-phenylalanine (FMLP), phagocytosis, and killing of bacteria in vitro. The concentration of saliva in the reaction mixture that caused a complete inhibition of the CL response of PMNs to both S. epidermidis and FMLP was 25%. However, there was no catalase or superoxide dismutase activity in saliva that could influence the CL response of PMNs. The production of superoxide by PMNs stimulated with S. epidermidis was assayed in the presence or absence of saliva by inhibition of the reduction of cytochrome c by superoxide dismutase. In the presence of 50% saliva, O2- generation by PMNs was only 7.3% of that observed in the absence of saliva. After gel filtration of salivary material through Sephadex G-25 or Sephacryl S-200, several fractions were obtained that inhibited the CL response of PMNs to either FMLP or S. epidermidis or to both. Two inhibitory fractions were analyzed. One contained immunoglobulin A, and the other contained a peptide which was composed of 14 different amino acids. The two fractions of high molecular weight included in the first protein peak of Sephacryl S-200 gel filtration were able to inhibit the CL response to S. epidermidis and to inhibit phagocytic activity, while fractions of low molecular weight (under 12,500 Mr) inhibited the CL response to FMLP and to S. epidermidis but did not inhibit phagocytic activity.